Social scholarship revisited: Changing scholarly practices in the age of social media. (18th March 2019) - Greenhow, Christine; Gleason, Benjamin; Staudt Willet, K. Bret
Abstract: This conceptual exploration revisits a key question from earlier work (Greenhow & Gleason, 2014): What is scholarship reconsidered in the age of social media? Social scholarship is a framework that expanded Boyers' (1990) conceptualization of scholarship to consider how social media affect discovery and research, teaching and learning, integration, and application. This paper critically reflects on how social scholarship continues to evolve in light of changing understandings in the field of educational technology and the role social media play in the academy. We provide recent examples of social scholarship such as altmetrics, interdisciplinary projects, crowdsourced educational technology syllabi and reconsideration of the needs of research participants. Moreover, we share concrete examples of how scholars might enact social scholarship, with what benefits and challenges, and surface new concerns regarding openness, equity, access, literacy, privacy and ethical considerations. Our paper concludes with recommendations for preparing scholars to enact social scholarship while mitigating the challenges it poses.